2013
DOI: 10.1089/fpd.2012.1217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Therapeutical and Reduced Levels of Antibiotics on the Fraction of Antibiotic-Resistant Strains of Escherichia coli in the Chicken Gut

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The results obtained show a significant increase by 16-fold in MIC values of amoxicillin for E. coli isolated from the group that received amoxicillin. These results are similar to those obtained by Van der Horst et al who showed that the addition of amoxicillin, enrofloxacin, or oxytetracycline in the chicken's drinking water induced the selection for resistant E. coli [ 32 ]. Similarly, Miranda et al and Simoneit et al reported that the administration of amoxicillin or other antibiotics in drinking water induced the selection and development of antimicrobial resistance in E. coli strains from chickens [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…The results obtained show a significant increase by 16-fold in MIC values of amoxicillin for E. coli isolated from the group that received amoxicillin. These results are similar to those obtained by Van der Horst et al who showed that the addition of amoxicillin, enrofloxacin, or oxytetracycline in the chicken's drinking water induced the selection for resistant E. coli [ 32 ]. Similarly, Miranda et al and Simoneit et al reported that the administration of amoxicillin or other antibiotics in drinking water induced the selection and development of antimicrobial resistance in E. coli strains from chickens [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…The exposure to concentrations that simulate those during antibiotic therapy for a similar amount of time led to a consistent and lasting increase in the MIC, severely altering the susceptibility of the strain. A similar conclusion was reached in an in vivo situation when studying flock treatment of chickens [ 31 ]. Obviously, the best way to prevent these course of events is to render the initial treatment fail-proof by increasing the concentration to a level that ascertains the death of all pathogens.…”
Section: Discussionsupporting
confidence: 75%
“…The observed increase in ampicillin resistance in broilers after amoxicillin treatment was in accordance with findings in previous studies. 11 , 24 Resistance rates to agents from other antibiotic classes (tetracyclines, aminoglycosides, sulfonamides, quinolones, and macrolides) also increased. Similarly, Jiménez-Belenguer et al 24 found increased resistance to tetracycline, aminoglycosides, and chloramphenicol after amoxicillin treatment.…”
Section: Discussionmentioning
confidence: 99%